উৎপাদকে বিশ্লেষণ
# নিচের সমীকরনসমুহ উৎপাদকে বিশ্লেষন করঃ
১। 3x - 75x3 ২। 4x2 - y2 ৩। 3ay2 - 48a
৪। a2 - 2ab + b2 - p2 ৫। 16y2 - a2 - 6a - 9 ৬। 8a + ap3
৭। 2a3 +16b3 ৮। x2 + y2 - 2xy -1 ৯। a2 - 2ab + 2b -1
১০। x4 - 6x2 +1 ১১। 36 -12x + x2 ১২। x6 - y6
১৩। (x - y)3 + z3 ১৪। 64x3 -8y3 ১৫। x2 +14x + 40
১৬। x2 + 7x -120 ১৭। x2 - 51x + 650 ১৮। a2 + 7ab +12b2
১৯। p2 + 2 pq -80b2 ২০। x2 - 3xy - 40y2 ২১। (x2 - x)2 + 3(x2 - x) - 40
২২। (a2 + b2 )2 -18(a2 + b2 ) -88 ২৩। (a2 + 7a)2 -8(a2 + 7a) -180
২৪। x2 + (3a + 4b)x + (2a2 + 5ab + 3b2 ) ২৫। 6x2 - x -15
২৬। x2 - x - (a +1)(a + 2) ২৭। 3x2 +11x - 4
২৮। 3x2 -16x -12 ২৯। 2x2 - 9x - 35 ৩০। 2x2 - 5xy + 2y2
৩১। x3 - 8(x - y)3 ৩২। 10p2 +11pq - 6q2 ৩৩। 2(x + y)2 - 3(x + y) - 2
৩৪। ax2 + (a2 +1)x + a ৩৫। 15x2 -11xy -12y2 ৩৬। a3 - 3a2b + 3ab2 - 2b3
১। 3x - 75x3
সমাধান :
3x - 75x3
= 3x(1- 25x2 )
= 3x{(1) - (5x)2}
= 3x(1+ 5x)(1- 5x)
২। 4x2 - y2
সমাধানঃ
4x2 - y2
=(2x)2-y2
=(2x+y)(2x-y)
৩। 3ay2 - 48a
সমাধানঃ
3ay2 - 48a
=3a(y2 – 16)
=3a(y2-42)
=3a(y-4)(y+4)
৪। a2 - 2ab + b2 - p2
সমাধানঃ
a2 - 2ab + b2 - p2
= (a - b)2 - p2
=(a-b+p)(a-b-p)
৫। 16y2 - a2 - 6a - 9
সমাধানঃ
16y2 - a2 - 6a – 9
=(4y)2 –( a2 + 2.a.3 – 32)
=(4y)2-(a+3)2
={(4y+(a+3)}{(4y-(a+3)}
=(4y+a+3)(4y-a-3)
৬। 8a + ap3
সমাধানঃ
8a + ap3
=a(8 + p3)
=a(23+pp3)
=a(2+p)(22+2.p+p2)
=a(2+pp)(4+2p+pp2)
৭। 2a3 +16b3
সমাধানঃ
2a3 +16b3
=2(a3 +8b3)
=2{a3+(2b)3}
=2(a+2b){(a)2+a.2b+(2b)2}
=2(a+2b)(a2+2ab+4b2)
৮। x2 + y2 - 2xy -1
সমাধানঃ
x2 + y2 - 2xy -1
= x2 - 2xy+ y2 -1
=(x-y)2-12
=(x-y+1)(x-y-1)
৯। a2 - 2ab + 2b -1
সমাধানঃ
a2 - 2ab + 2b -1
= (a2 -1)- 2b(a -1)
=(a-1)(a+1)-2b(a-1)
=(a-1)(a+1-2b)
১০। x4 - 6x2 +1
সমাধানঃ
x4 - 6x2 +1
=(x2 )2 – 2.x2 .1+12-4x2
=(x2-1)2-(2x)2
=(x2-1+2x)(x2-1-2x)
১১। 36 -12x + x2
সমাধানঃ
36 -12x + x2
=x2-2.x.6+62
=(x-6)2
=(x-6)(x+6)
১২। x6 - y6
সমাধানঃ
x6 - y6
=(x3)2-(y3)2
=(x3+Y3)( x3-Y3)
=(X+Y)(X2-XY+Y2)(X-Y)(X2+XY-Y2)
=(X+Y) (X-Y)( (X2-XY+Y2) X2+XY-Y2)
১৩। (x - y)3 + z3
সমাধানঃ
(x - y)3 + z3
={(x - y) + z}{(x-y)2-(x-y)z+z2}
=(x-y+z)(x2-2xy+y2-xz+yz+z2)
১৪। 64x3 -8y3
সমাধানঃ
64x3 -8y3
=8(8x3 -y3)
=8{(2x)3-y3)}
=8(2x-y){(2x)2+2.x.y+(y)2}
=8(2x-y)(4x2+2xy+y2)
১৫। x2 +14x + 40
সমাধানঃ
x2 +14x + 40
= x2 +4x+10x + 40
=x(x+4)+10(x+4)
=(x+4)(x+10)
১৬। x2 + 7x -120
সমাধানঃ
x2 + 7x -120
= x2 + 15x-8x -120
=x(x+15)-8(x+15)
=(x-8)(x+15)
১৭। x2 - 51x + 650
সমাধানঃ
x2 - 51x + 650
= x2 - 26x-25x + 650
=x(x-26)-25(x-26)
=(x-25)(x-26)
১৮। a2 + 7ab +12b2
সমাধানঃ
a2 + 7ab +12b2
= a2 + 3ab+4ab +12b2
=a(a+3b)+4b(a+3b)
=(a+4b)(a+3b)
১৯। p2 + 2 pq -80b2
সমাধানঃ
p2 + 2 pq -80b2
= p2 + 10pq-8pq -80b2
=p(p+10q)-8q(p+10q)
=(p-8q)(p+10q)
২০। x2 - 3xy - 40y2
সমাধানঃ
x2 - 3xy - 40y2
= x2 - 8xy+5xy - 40y2
=x(x-8y)+5y(x-8y)
=(x+5y)(x-8y)
২১। (x2 - x)2 + 3(x2 - x) – 40
সমাধানঃ
মনে করি, x2 – x=a
প্রাপ্ত রাশি=a2+3a-40
= a2+8a-5a-40
=a(a+8)-5(a+8)
=(a-5)(a+8)
=(x2-x-5)(x2-x+8) [মান বসিয়ে]
২২। (a2 + b2 )2 -18(a2 + b2 ) -88
সমাধানঃ
ধরি, a2 + b2=x
প্রদত্ত রাশি=x2-18x-88
= x2-22x+4x-88
=x(x-22)+4(x-22)
=(x+4)(x-22)
=( a2 + b2+4)( a2 + b2-22)
২৩। (a2 + 7a)2 -8(a2 + 7a) -180
সমাধানঃ
মনে করি, a2 + 7a=x
প্রদত্ত রাশি=x2-8x-180
= x2-18x+10x-180
=x(x-18)+10(x-18)
=(x+10)(x-18)
=( a2 + 7a+10)( a2 + 7a-18)
২৪। x2 + (3a + 4b)x + (2a2 + 5ab + 3b2 )
সমাধানঃ
x2 + (3a + 4b)x + (2a2 + 5ab + 3b2 )
= x2 + (3a + 4b)x + (2a2 + 3ab+2ab + 3b2 )
= x2 + (3a + 4b)x +{a(2a+3b)+b(2a+3b)
= x2 + (3a + 4b)x +(a+b)(2a+3b)
= x2 + (2a + 3b)x+(a+b)x +(a+b)(2a+3b)
=x(x+2a+3b)+(a+b)(x+2a+3b)
=(x+a+b)(x+2a+3b)
২৫। 6x2 - x -15
সমাধানঃ
6x2 - x -15
=6x2 - 10x+9x -15
=2x(3x-5)+3(3x-5)
=(2x+3)(3x-5)
২৬। x2 - x - (a +1)(a + 2)
সমাধানঃ
x2 - x - (a +1)(a + 2)
= x2 - x - (a +1)(a + 1+1)
= x2 - x - m(m+1) [a+1=m ধরে]
=x2-x-m2-m
= x2-m2-x-m
=(x-m)(x+m)-1(x+m)
=(x+m)(x-m-1)
=(x+a+1)(x-a-1-1) [মান বসিয়ে]
=(x+a+1)(x-a-2)
২৭। 3x2 +11x – 4
সমাধানঃ
3x2 +11x – 4
=3x2 +12x-x – 4
=3x(x+4)-1(x+4)
=(3x-1)(x+4)
২৮। 3x2 -16x -12
সমাধানঃ
3x2 -16x -12
=3x2 -18x-2x -12
=3x(x-6)-2(x-6)
=(3x-2)(x-6)
২৯। 2x2 - 9x - 35
সমাধানঃ
2x2 - 9x – 35
=2x2 - 14x-5x – 35
=2x(x-7)-5(x-7)
=(2x-5)(x-7)
৩০। 2x2 - 5xy + 2y2
সমাধানঃ
2x2 - 5xy + 2y2
=2x2 - 4xy-xy + 2y2
=2x(x-2y)-y(x-2y)
=(2x-y)(2x-y)
৩১। x3 - 8(x - y)3
সমাধানঃ
x3 - 8(x - y)3
= (x)3 – {2(x - y)}3
=(x)3 – {2x -2 y}3
={x-(2x-2y){(x)2+x(2x-2y)+(2x-2y)2}
=(x-2x+2y){x2+2x2-2xy+(2x)2-2.2x.2y+(2y)2}
=(x-2x+2y)( 3x2-2xy+4x2-8x.y+4y2)
=(2y-x)(7x2-10xy+4y2)
৩২। 10p2 +11pq - 6q2
সমাধানঃ
10p2 +11pq - 6q2
=10p2 +15pq-4pq - 6q2
=5p(2p+3q)-2q(2p+3q)
=(5p-2q)(2p+3q)
৩৩। 2(x + y)2 - 3(x + y) – 2
সমাধানঃ
ধরি, x+y=a
প্রদত্ত রাশি=2(a)2 - 3(a) – 2
=2a2 - 4a+a – 2
=2a(a-2)+1(a-2)
=(2a+1)(a-2)
=(2x+2y+1)(x+y-2)
৩৪। ax2 + (a2 +1)x + a
সমাধানঃ
ax2 + (a2 +1)x + a
= ax2 + a2 x+x + a
=ax(x+a)+1(x+a)
=(ax+1)(x+1)
৩৫। 15x2 -11xy -12y2
সমাধানঃ
15x2 -11xy -12y2
=15x2 -20xy+9xy -12y2
=5x(3x-4y)+3y(3x-4y)
=(3x-4y)(5x+3y)
৩৬। a3 - 3a2b + 3ab2 - 2b3
সমাধানঃ
a3 - 3a2b + 3ab2 - 2b3
= a3 - 3a2b + 3ab2 - b3-b3
=(a-b)3-b3
=(a-b-b){(a-b)2+(a-b).b+b2}
=(a-2b)(a2-2ab+b2+ab-b2+b2)
=(a-2b)(a2-ab+b2)
No comments:
Post a Comment